Mechanism analysis of grain growth dominated by alloy composition gradients during powder bed fusion - Yao, Liming (2023)
A multi-physics simulation model has been established to investigate the influence of Laser powder bed fusion parameters on the spatial composition distribution and grain growth mechanism of the single-track printed dissimilar alloys. Our study shows that alloy composition gradient isosurfaces can be used to visualize the spatial distribution of alloy composition for miscible dissimilar alloys. When the melt pool aspect ratio changes from large to small, the grain growth transitions from the temperature gradient mode to composition gradient mode and then to the mixed mode. Our experimental observations show that in extreme cases, the curved grain angle can reach 272°.